Orientation of Carbon Fibers in Copper matrix Produced by Powder Injection Molding - ., M Irfan Shirazi, Faiz Ahmad, M Rafi Raza, Ali S Muhsan, MA Omer, (2014)
Fiber orientation is a big challenge in short fiber reinforced composites. Powder injection molding (PIM) process has some intrinsic fiber alignment associated with it. During PIM process fibers in skin region of moldings are aligned as these regions experience higher shear flow caused by the mold walls. Fibers in the core region remain randomly aligned as these regions are far from mold walls and experience lesser shear flow. In this study short carbon fiber (CF) reinforced copper matrix composite was developed by PIM process. Two copper composite feedstock formulations were prepared having 5 vol% and 10 vol% CFs and a wax based binder system. Fiber orientation was controlled during injection molding by using a modified mold that has a diverging sprue. The sprue creates converging flow when feedstock enters into the mold cavity. Fiber orientation was analysed after molding using FESEM. The orientation of fibers can be controlled by controlling flow of feedstock into the mold.